1992
DOI: 10.1182/blood.v80.7.1765.1765
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous immunophenotype of granular lymphocyte expansions: differential expression of the CD8 alpha and CD8 beta chains [see comments]

Abstract: In this study, we have evaluated 14 large granular lymphocyte (LGL) expansions, 11 of which were CD8+. Analysis of the membrane expression of the alpha and beta chains of the CD8 antigen, using specific monoclonal antibodies (MoAbs), has shown that LGL expansions with the CD3+, CD4+, CD8+, CD57+ T-cell receptor (TcR) alpha beta phenotype bear the CD8 alpha/alpha isoform, while the CD3+, CD4-, CD8+, CD57+ TcR alpha beta samples were positive for both the CD8 alpha and CD8 beta chains. These data were confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Immunofluorescence analysis of cell surface antigen expression. Flow cytometric analyses of total CLL mononuclear cells and of T-cell-enriched fractions were performed by one-, two-or three-colour immunofluorescence, as previously described (de Totero et al, 1992). Briefly, direct immunofluorescence labelling was carried out with anti-CD2, -CD19, -CD3, -TCRa/b, -CD4, -CD8, -CD57, -CD16, -DR (all from Becton Dickinson), -CD30 (Dakopatts, Glostrup, Denmark) and anti-CD14 (Ortho) moAbs labelled with fluorescein (FITC) or with anti-CD28 moAb labelled with phycoerythrin (PE) (Becton Dickinson), and 1 × 10 5 cells/sample were incubated with the labelled antibody for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence analysis of cell surface antigen expression. Flow cytometric analyses of total CLL mononuclear cells and of T-cell-enriched fractions were performed by one-, two-or three-colour immunofluorescence, as previously described (de Totero et al, 1992). Briefly, direct immunofluorescence labelling was carried out with anti-CD2, -CD19, -CD3, -TCRa/b, -CD4, -CD8, -CD57, -CD16, -DR (all from Becton Dickinson), -CD30 (Dakopatts, Glostrup, Denmark) and anti-CD14 (Ortho) moAbs labelled with fluorescein (FITC) or with anti-CD28 moAb labelled with phycoerythrin (PE) (Becton Dickinson), and 1 × 10 5 cells/sample were incubated with the labelled antibody for 30 min on ice.…”
Section: Methodsmentioning
confidence: 99%
“…The mean percentage of CD8 þ / CD28 ¹ /CD30 þ cells was 33 Ϯ 9·8%. Since LGL-like T cells do not express the CD28 antigen (de Totero et al, 1992), it is conceivable that a large fraction of the CD30 þ cells detected following PHA activation was representative of this subset.…”
Section: Cd28 Expression On Cd30 þ T Cellsmentioning
confidence: 99%
“…Unlike normal thymic DP cells and the majority of CD8 SP T cells, both of which express heterodimeric a/b subunits, a subpopulation of NK cells and T lymphocytes expresses a CD8 aa homodimer. Isoform analysis of the three present CD4/CD8 DP patients, who had low CD8 expression, revealed that their CD8 was composed of a CD8aa homodimer, as in some DP T-LGL patients previously reported (de Totero et al, 1992;Mizuki et al, 1998). CD4 SP cells can reacquire CD8 and become CD4 + CD8 dim T cells, in response to physiological stimuli, because the CD8 genes in CD4 cells are unmethylated.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, most CD8^ cells among intermediate TCR cells in mice have the aa homodimer of CD8 antigens [5]. Similarly, it has been reported that CD57 ' T cells in humans also have the an homodimer of CD8 antigens [37]. Namely.…”
Section: Discussionmentioning
confidence: 99%